Aplikasi Sistem Pendukung Keputusan Penerimaan Karyawan Baru dengan Metode Simple Additive Weighting (SAW) - Prayogo, Triadi; Cleopatra, Maria; Irawan, Ari (Jurnal Informatika Universitas Pamulang, 2020)
The problem of several agencies or companies in determining employees or new employees is how the institution can select qualified new employees where currently the recruitment of each applicant candidate to be accepted at the company more applicants in the available vacancies. HRD will be selective in screening prospective employees who can be relied on to fill important parts of the company specifically the section provided for the right people and providing the required qualifications. The need for fast and precise information also needs to be applied by PT Abacus Dana Pensiuntama in the recruitment of new employees to be able to select and provide competent human resources for their fields. Research is offered to use the method in the decision making process on the recruitment of prospective new employees. To support the decision making process, a weighted sum method is used. The research method used is the foundation of research and observation. This decision making process will produce optimal decisions in determining the prospective employees who are entitled to the company in accordance with the results of the calculation by the weighted sum method.